Artificial intelligence applicated in gastric cancer: A bibliometric and visual analysis via CiteSpace - Zhang, Guoyang; Song, Jingjing; Feng, Zongfeng; Zhao, Wentao; Huang, Pan; Liu, Li; Zhang, Yang; Su, Xufeng; Wu, Yukang; Cao, Yi; Li, Zhengrong; Jie, Zhigang (Frontiers in Oncology, 2023)
Objective: To analyze and visualize the current research focus, research frontiers, evolutionary processes and trends of artificial intelligence (AI) in the field of gastric cancer using a bibliometric analysis. Methods: The Web of Science Core Collection database was selected as the data source for this study to retrieve and obtain articles and reviews related to AI in gastric cancer. All the information extracted from the articles was imported to CiteSpace to conduct the bibliometric and knowledge map analysis, allowing us to clearly visualize the research hotspots and trends in this field. Results: A total of 183 articles published between 2017 and 2022 were included, contributed by 201 authors from 33 countries/regions. Among them, China (47.54%), Japan (21.86%) and the USA (13.11%) have made outstanding contributions in this field, accounting for 82.51% of the total publications. The primary research institutions were Wuhan University, Tokyo University and Tada Tomohiro Inst Gastroenterol & Proctol. TADA T (n = 12) and HIRASAWA T (n = 90) were ranked first in the top ten authors and co-cited authors. GASTROINTESTINAL ENDOSCOPY (21 publications; IF 2022, 9.189; Q1) was the most published journal, while GASTRIC CANCER (133 citations; IF 2022, 8.171; Q1) was the most co-cited journal. Nevertheless, the cooperation between countries and institutions should be further strengthened. The most common keywords were AI, gastric cancer, convolutional neural network. The "deep learning algorithm" started to burst in 2020 and continues till now which indicated that this research topic has attracted continuous attention in recent years and would be the trend of research on AI application in GC. Conclusions: Research related to AI in gastric cancer is increasing exponentially. Current research hotspots focus on the application of AI in gastric cancer, represented by convolutional neural networks and deep learning, in diagnosis and differential diagnosis and staging. Considering the great potential and clinical application prospects, the related area of AI applications in gastric cancer will remain a research hotspot in the future.